HATUHAHA AMARIMA LOU NUSA DALAM PERSPEKTIF FILSAFAT KEBUDAYAAN CORNELIS ANTHONIE VAN PEURSEN DAN RELEVANSINYA DENGAN KEUTUHAN BANGSA INDONESIA - Jannes Alexander Uhi; Sri Soeprapto; Muhammad Mukhtasar Syamsuddin (Jurnal Filsafat "WISDOM", 2016)
Hatuhaha Amarima Lou Nusa refers to an indigenous group that has a specific culture from ancestors to contemporary times. The content of cultural values of Hatuhaha Amarima is important to be applied to the context of the daily lives of Hatuhaha Amarima Lou Nusa's people in particular and Indonesia in general. This paper aims to reveal the dynamics of historical and cultural forms of Hatuhaha Amarima, and to explore the nature of Hatuhaha Amarima, along with the values which contained in it with Cornelis Anthonie van Peursen's philosophy of culture perspective. The essence of Hatuhaha Amarima are contained with society (human), history, territory, customs and culture, and language. As the result, the study explaints the epistemologycal aspect of Hatuhaha Amarima in its realistic nature. Also, the study finds a cultural polarization of Hatuhaha Amarima that is as monodualistic in its nature, so it is presenting the feel of living together in multiculturalism with relative condition; ethnicity, religion, and culture. One of the most important point of culture that was passed on by people of Hatuhaha Amarima is the relation of I – You. This is existing in the context of kinship systems, family systems and brotherhood. Obviously, the cultural values of Hatuhaha Amarima has tighted connection with Bhineka Tunggal Ika's principles, so that it is important to applicate it to the context of the state living integrity and nation in Indonesia. The soul of cultural values of Hatuhaha Amarima represented of the ideal values of Pancasila and universal values.